Trees on the farm : assessing the adoption potential of agroforestry practices in Africa - Franzel, Steven Charles; Scherr, Sara J. (CABI Pub. in association with the International Centre for Research in Agroforestry, 2002)
This book assesses the adoption of selected agroforestry practices developed with African farmers, describing methods, and drawing out the implications for research, development and policy. Five case studies conducted in Kenya and Zambia to evaluate the adoption potential of agroforestry are included. The cases illustrate methods of farm and village technology design, testing and analysis that are applicable to a wide range of natural resource management practices. Along with the case studies, the contents also include chapters on: the methods for assessing agroforestry adoption potential; promoting new agroforestry technologies; policy lessons from on-farm research and assessing adoption potential; and the lessons learned and future directions.